Connection between some kinematic parameters and successful performance of the Tsukahara jump - Kajic, E.; Ðuzel. J.; Brnicevic, M. M. (Sport Science - International Scientific Journal of Kinesiology, 2020)
The aim of this study was to determine the influence of kinematic parameters, morphological measures and some motor tests on the success of performing a complex element on the jump - the Tsukahara jump. For this purpose, a study was conducted on a sample of 10 young gymnasts aged 12 to 14 years. In total, ten kinematic variables obtained by video were analyzed. Each respondent jumped three jumps, whose attempts were recorded in the preparation of the national team in Cakovec. The results were processed by regression analysis, which found that there was a significant multiple correlations between the set of kinematic parameters and the Tsukahara jump. The individual influence of six kinematic parameters on the criterion variable was also determined.